The influence of the mechanical behaviour of the middle ear ligaments: a finite element analysis - Fernanda Gentil (2011)
The interest in computer modelling of biomechanical systems, mainly by using the finite element method (FEM), has been increasing, in particular for analysis of the mechanical behaviour of the human ear. In this work, a finite element model of the middle ear was developed to study the dynamic structural response to harmonic vibrations for distinct sound pressure levels applied on the eardrum. The model includes different ligaments and muscle tendons with elastic and hyperelastic behaviour for these supportive structures. Additionally, the nonlinear behaviour of the ligaments and muscle tendons was investigated, as they are the connection between ossicles by contact formulation. Harmonic responses of the umbo and stapes footplate displacements, between 100 Hz and 10 kHz, were obtained and compared with previously published work. The stress state of ligaments (superior, lateral, and anterior of malleus and superior and posterior of incus) was analysed, with the focus on balance of the supportive structures of the middle ear, as ligaments make the link between the ossicular chain and the walls of the tympanic cavity. The results obtained in this work highlight the importance of using hyperelastic models to simulate the mechanical behaviour for the ligaments and tendons.